1993
DOI: 10.1021/tx00033a017
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantitation of benzo[a]pyrene-DNA adducts formed in mouse skin

Abstract: The DNA adducts of benzo[a]pyrene (BP) formed in vitro were previously identified and quantitated. In this paper, we report the identification and quantitation of the depurination adducts of BP, 8-(benzo[a]pyren-6-yl)guanine (BP-6-C8Gua), BP-6-N7Gua, and BP-6-N7Ade, formed in mouse skin by one-electron oxidation, as well as the major stable adduct formed via the diolepoxide pathway, BP diolepoxide bound at C-10 to the 2-amino of dG (BPDE-10-N2dG). Identification of the depurination adducts was achieved by HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
135
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(149 citation statements)
references
References 18 publications
13
135
1
Order By: Relevance
“…BPDE forms predominantly stable DNA adducts [22,86] and it formed the most number of tumors when early S-phase liver cells were exposed [48]. This result is consistent with studies suggesting that NER of the BPDEinduced stable adducts is error-free [45,54], and that mutations are induced in the proliferating cells by errors in translesion synthesis.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…BPDE forms predominantly stable DNA adducts [22,86] and it formed the most number of tumors when early S-phase liver cells were exposed [48]. This result is consistent with studies suggesting that NER of the BPDEinduced stable adducts is error-free [45,54], and that mutations are induced in the proliferating cells by errors in translesion synthesis.…”
Section: Introductionsupporting
confidence: 87%
“…Taken together, it appears that the PAH or their metabolites that form predominantly depurinating adducts may form preneoplastic mutations by error-prone repair in quiescent cells, whereas the PAH that form mainly stable adducts would induce mutations by errors in translesion synthesis in proliferating cells. PAH such as BP, which forms significant amounts of both types of adducts [22,86], appear to induce mutations from both stable and depurinating adducts. For example, the relative proportions of BP-induced depurinating adducts show a strong correlation with the relative abundance of Adeor Gua-specific oncogenic H-ras mutations in skin tumors [16].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism of PAHs through one electron oxidation resulting in reactive free radical intermediates that can react with DNA to form DNA covalent adducts has also been reported (28)(29)(30)(31)(32) (Figure 2). Due to differences in mechanisms of metabolic activation, the ultimate carcinogenic metabolites or intermediates as well as the types of DNA adducts formed from the diolepoxide formation or from the free radical generation are different.…”
Section: A Mammalian Metabolic Activation Of Pahsmentioning
confidence: 77%
“…PAH are ubiquitous environmental contaminants that result from incomplete combustion processes and are known carcinogens [8]. PAH are thought to exert their carcinogenic properties through their ability to form PAH-DNA adducts [9][10][11]. Both casecontrol [12] and cohort [13] studies have found that most jobs associated with occupational PAH exposure have the potential for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%